PENGARUH KEPEMIMPINAN, DISIPLIN DAN KOMPENSASI TERHADAP KINERJA GURU SD NEGERI 69 KOTA BENGKULU - Dewi, Ratih Komala (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2018)
The findings of this study were to determine the effect of Leadership, Compensation and Discipline on the performance of teachers in elementary school 69 of Bengkulu City . Data collection methods used were observation and distribution of questionnaires to 48 elementary school teachers in elementary school 69 of Bengkulu city. Quantitative data analysis method is done by looking for the scoring of data scaling (scoring), while the qualitative method of data analysis is done by processing SPSS 22 software data with F test statistics and t test statistics and drawing conclusions and verification of data. The results of this study indicate that leadership roles, Compensation and Discipline have a significant effect simultaneously and have relevance to teacher performance. The principal has the task of fostering the teachers related to their main tasks, namely teaching students so that they achieve optimal performance. Furthermore, the principal as a person who is used as a role model can provide examples of teaching and learning activities in front of the class and high work discipline so that the teacher can imitate and practice in carrying out daily tasks and improve the discipline of each teacher. On the other hand, the findings of this study indicate that teachers who have received compensation in the form of teacher professional allowances have better performance than teachers who have not received teacher professional allowances. Based on the results of research conducted in Elementary School 69 of bengkulu city, compensation has the most dominant influence on teacher performance.